Rehabilitation of degraded tropical forest ecosystems project - Kobayashi, S.; Turnbull, J.W.; Cossalter, C. (Center for International Forestry Research, 2001)
Tropical forests are being cleared at a rate of 16.9 million hectares per year and timber harvesting results in over 5 million hectares becoming secondary forests annually without adequate management. This decrease and degradation affect both timber production and many environmental values. Selective and clear cutting, and burning are major causes of land degradation. An assessment is needed of harvesting impacts that influence rehabilitation methods. The harvesting impacts on ecosystems vary with time and methods of logging, timber transporting methods, logged tree species, soil characteristics, topographies, local rainfall patterns etc., and must be assessed in a range of conditions with long term monitoring. Increased supply of wood from plantation forests has the potential to reduce pressure on natural forest resources as well as contributing to environmental care and economic advancement for landholders. Short-rotation plantations can result in changes in nutrient storage and cycling processes due to factors such as harvesting wood, fertilisation, erosion, leaching, and modified patterns of organic matter turnover. These factors can affect storage and supply of soil nutrients for tree growth and consequently the sustainability of plantation systems. Opportunities exist to manipulate soil organic matter through silvicultural practices but these must be technically feasible, economically viable and socially acceptable. The following research objectives are proposed: (1). evaluation of forest harvesting and fire impacts on the forest ecosystems, (2). development of methods to rehabilitate logged-over forests, secondary forests and degraded forest lands, (3). development of silvicultural techniques on plantation and degraded lands, (4). network on the rehabilitation of degraded tropical forest ecosystems. It is anticipated that the results of these studies will contribute to the sustainable use of forest resources and environmental conservation.